(untitled) (Italiano LinguaDue, 2020)
Il seguente articolo analizza una prova di ascolto di italiano LS di livello C1, apparsa nella sessione invernale 2016 della certificazione CILS (Università per Stranieri di Siena). L’analisi è condotta su più campioni, sia di apprendenti di italiano [di livello C1 (n=70) e di livello B1 (n=67)] che di nativi [liceali (n=88) ed esperti (n=62)]. L’esito della ricognizione attesta criticità di diverso genere. Investigation into the validity of a CILS level C1 listening test This paper deals with a test C1 level listening which appeared in the 2016 winter session of CILS Certificate (University for Foreigners, Siena). The study refers to different populations, including both students of Italian as a FL [C1 level (n=70) and B1 level (n=67)] and natives [students at secondary School (n=88); highly proficient natives (n=62)]. Our analysis detects different problems.